YUNON BAQTRIYA DAVLATI HAQIDA MA’LUMOT BERUVCHI ANTIK DAVR MANBALARI TAHLILI - Abdushukurov Lazizbek, Elmurodov Dilshod, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article is devoted to the analysis of the historical sources of the Greco-Bactrian state. Information about Greco-Bactrian culture, political processes, and economic development is reflected in the works of ancient historians, numismatic sources, archaeological finds, and local inscriptions. The study thoroughly analyzes the specifics of these sources, their role in illuminating historical truth, and their scientific value. The contribution of this state to the civilizations of Central Asia is also highlighted.